P6.061 Development of a Validated Questionnaire For HIV Attendees. (13th July 2013) - Land, L; Sizmur, S; Harding, J; Ross, J D C
Abstract : Background: Patients are becoming more actively involved in decisions about their care and have greater influence to change and improve the quality of services by reporting their experiences. Within HIV services, positive experiences increase engagement with services and have been linked to higher levels of treatment adherence. A previous systematic review assessing satisfaction with care failed to locate a gold standard method of measuring satisfaction in this setting. Aim to design a specific HIV patient satisfaction questionnaire Methods Four work streams were employed to develop and test a new questionnaire. Firstly, key themes identified in the systematic review were used as a topic guide for focus group discussion to assess their relevance and importance. Four focus groups comprising 32 participants were conducted and revealed the importance of physician knowledge and expertise; dignity, autonomy and respect; and good communication. The second stream involved interviews with ten patients, exploring their motivation to complete a questionnaire. Thirdly, data from the focus groups and interviews were used to develop an initial questionnaire which was cognitively tested on a further ten patients, this provided face validity for the questionnaire design, layout and wording. The final stream employed a pilot study of the questionnaire with 80 clinic attendees. Results: The pilot survey demonstrated that there was a high completion rate. Two questions were modified and additional routing instructions were added. Pairwise correlations reflected the thematic structure of the questionnaire and supported good criterion validity. Conclusions: The combination of a systematic analysis of previous patient survey tools, focus group discussions and cognitive testing of the questionnaire was used to ensure high content validity. The questionnaire was found to be acceptable to patients and a high completion rate was attained without the use of a financial incentive.